Harmonizing culture, religion, and professional nursing standards: the malay-muslim-friendly development of nursing uniforms at Hospital Pusrawi, Malaysia, 1984–2018 - Saidun, Salilah; Akhmetova, Elmira; Awang Abdul Rahman, Amilah (Taylor and Francis Ltd., 2020)
This study describes the efforts of Hospital Pusrawi Sdn Bhd, Malaysia, to integrate local culture, religion, and standards of good nursing practices in the design of its nursing uniform from 1984 until 2018. The study is based on the analysis of the hospital’s institutional archives and on interviews with retired or senior nurses and administrators. The hospital’s endeavor in integrating culture, religion, and nursing practice proved to be challenging due to their contradictory natures. Clinical dress code recommends short sleeves to facilitate hand hygiene and infection control, the use of non-dangling attire to prevent cross-contamination, and non-movement-restrictive workwear whereas Malay-Muslim women prefer long sleeves, headscarves, and ankle-length skirts. The strategies used to overcome the challenges may serve as potential exemplary solutions for other healthcare institutions that are motivated to accommodate the religious or cultural clothing needs of their staff members without compromising the standards of good practices in healthcare.